The Influence of Capital Structure, Profitability, and Good Corporate Governance on Greenwashing in Infrastructure Companies in Indonesia - Seprianti Seprianti; Siti Khairani (SAINTIS Publishing, 2025)
This research aims to analyze the influence of capital structure, profitability, and Good Corporate Governance (GCG) on greenwashing practices among infrastructure companies listed on the Indonesia Stock Exchange during 2023–2024. The independent variables used in this study consist of profitability (Return on Assets), capital structure (Debt to Equity Ratio), the frequency of board of commissioners’ meetings, the proportion of independent commissioners, and the presence of an audit committee. The findings reveal that capital structure exerts a significantly negative effect on greenwashing practices. Meanwhile, profitability, the proportion of independent commissioners, the number of board meetings, and the existence of an audit committee show negative but statistically insignificant effects on greenwashing. Taken together, all independent variables collectively have a significant influence on greenwashing, with a coefficient of determination of 43.6%. These outcomes suggest that capital structure is the most influential determinant of greenwashing practices within Indonesia’s infrastructure sector, whereas the current implementation of GCG mechanisms has yet to effectively curb such practices.